Comparing ship versus plane-based personnel movement of Australian Antarctic expeditioners - Kimberley Norris; Ayton, J; Paton, D (2017)
The introduction of plane-based personnel movement within the Australian Antarctic programme via the intercontinental Antarctic Airlink to complement the existing ship-based transportation arrangements provided a unique opportunity to examine the impact of differing transportation methods on expeditioner health and well-being. This research investigated the response profiles of 88 Australian expeditioners who experienced different methods of transportation to and from Antarctica. Results indicated that the method of transportation to Antarctica had no significant impact on expeditioner well-being. In contrast, expeditioners who returned to Australia by plane reported significantly higher distress two-months post-return than those who returned by ship. However, there were no significant differences in expeditioner response profiles at 12-months post-return based on method of transportation. Implications of these findings for expeditioner training and support needs are discussed.